2019
DOI: 10.1029/2019jg005369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic and Massive Resuspension Mechanisms on the Microphytobenthos Dynamics in a Temperate Intertidal Mudflat

Abstract: Microphytobenthos (MPB) resuspension is a key mechanism in the transfer of organic matter from productive intertidal mudflats to terrestrial and marine systems. In this study, we infer on the contribution of physical and biological factors involved in the MPB resuspension. We use a physical‐biological coupled model forced by realistic meteorological and hydrodynamical forcings to simulate chronic (without any concomitant sediment resuspension) and massive (driven by bed failure) resuspension over a year. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 118 publications
(165 reference statements)
5
16
0
Order By: Relevance
“…The spatial and temporal distribution of MPB over mudflats is highly variable, as it is driven by highly variable physical [light, mud surface temperature (MST), tides, waves, and current] and biological (grazing, biostabilization, and bioturbation) conditions (e.g., Admiraal, 1984;Blanchard et al, 1996;MacIntyre et al, 1996;Underwood, 2001; Morris and Kromkamp, 2003;Sahan et al, 2007;Salleh and McMinn, 2011;Kwon et al, 2014;Orvain et al, 2014a,b;Savelli et al, 2019). Such a variability impedes any accurate and robust assessment of the role played by MPB at the scale of the whole mudflat ecosystem and of its contribution to the carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and temporal distribution of MPB over mudflats is highly variable, as it is driven by highly variable physical [light, mud surface temperature (MST), tides, waves, and current] and biological (grazing, biostabilization, and bioturbation) conditions (e.g., Admiraal, 1984;Blanchard et al, 1996;MacIntyre et al, 1996;Underwood, 2001; Morris and Kromkamp, 2003;Sahan et al, 2007;Salleh and McMinn, 2011;Kwon et al, 2014;Orvain et al, 2014a,b;Savelli et al, 2019). Such a variability impedes any accurate and robust assessment of the role played by MPB at the scale of the whole mudflat ecosystem and of its contribution to the carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, remotely sensed estimates of vegetation index and of in water MPB chlorophyll a (Chl a) concentration were compared to model outputs in order to assess the model ability to simulate realistic MPB biomass levels over the Brouage mudflat (Savelli et al, 2018(Savelli et al, , 2019. Such a comparison does not exist for MPB PP.…”
Section: Introductionmentioning
confidence: 99%
“…a and sediment concentrations on the salt marsh will be a product of water depth and wave energy (Leonardi et al, 2015). The wind speed values during this study were less that those found by de Jonge and van Beusekom (1995) to cause major resuspension, but even lower speeds can resuspend surface cells and sediments loosely associated in a "fluff " layer (Savelli et al, 2019). Such resuspension of biofilm material also weakens the potential for further biostabilization, leading to further resuspension (Ubertini et al, 2015).…”
Section: Discussionmentioning
confidence: 50%
“…a concentration in the top 2-mm sediment surface before and after high-tide emersion periods during spring tides on both the transition and the salt marsh. Other studies in the Colne estuary have found significant "wash away" from mudflats during tidal cover (Bellinger et al, 2009;Taylor et al, 2013), and modeling shows this can be a significant process in MPB biomass dynamics on mudflats (Savelli et al, 2019). High levels of microspatial variability in MPB biomass (Spilmont et al, 2011;Taylor et al, 2013) may mask individual localized losses on any particular patch of sediment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation